Efficacy of amniotic membrane with coronally advanced flap in the treatment of gingival recession: an updated systematic review and meta-analysis - Reham Abdel-Fatah; Wafaa Saleh (BMC, 2024)
Abstract Objectives This systematic review aims to evaluate the efficacy of combining the amniotic membrane (AM) with the coronally advanced flap (CAF) in the treatment of Miller class I and II gingival recession (GR). Methods The protocol of this updated PRISMA-compliant systematic review was registered in PROSPERO (CRD42023431501). The following treatment outcomes were recorded; recession depth (RD), recession width (RW), width of keratinized gingiva (WKG), and clinical attachment level (CAL). We searched the following databases: MEDLINE, Cochrane Library, Google Scholar, EMBASE, Web of Science, and Science Direct. Results Two independent reviewers screened the selected articles. Twenty-two eligible articles were extracted, with 689 sites of GR in 481 patients. No statistically significant difference was found in RD, RW, WKG, and CAL between (AM&CAF) in comparison to control groups. However, the subgroup analysis showed statistically significant differences in RD between the (AM & CAF) group v/s (CAF) alone (P = 0.004). Moreover, the subgroup analysis of the WKG showed statistically significant differences between (AM & CAF) v/s (CAF&CM) (p = 0.04). Additionally, a statistically significant difference was found in the subgroup analysis of CAL between both (AM & CAF) group v/s (CAF) alone (p = 0.0009). Conclusion With the limitations of this meta-analysis due to short follow-up periods (6 months), the AM can be considered a viable treatment option for GR defects with satisfactory treatment outcomes comparable to other previously investigated treatment modalities. Clinical significance While AM showed various beneficial properties as an ideal membrane for the coverage of GR, future studies are required to completely understand the potential application of AM in the treatment of GR.